N,N-Dimethylaminoxy Carbonyl, a Polar Protecting Group for Efficient Peptide Synthesis - Okamoto, Ryo; Ono, Emiko; Izumi, Masayuki; Kajihara, Yasuhiro (Frontiers in Chemistry, 2019)
Direct peptide coupling with minimum protection strategy is a straightforward method to couple peptide segments. In order to utilize this methodology, an efficient synthetic protocol of partially protected peptides, which could show poor solubility in various solvents, was essential. Herein, we describe a new protecting group, N,N-dimethylaminoxy carbonyl (Dmaoc) and an efficient peptide coupling strategy using 3,4-diaminobenzoyl (Dbz) group as a leaving group. The Dmaoc group containing the dimethylamino group was more polar than the tBoc group, which had been utilized as one of the protecting groups for Lys-ε-NH2. Intriguingly, Dmaoc was found to be removable by a reduction in the buffer containing thiol. On the other hand, we also found that the Dbz group could be used as a leaving group in the direct peptide bond formation through the formation of benzotriazol (Bt) group. The Dmaoc-protected peptide-Dbz, where the C-terminal was functionalized with Dbz, could be directly synthesized by standard protocol of Fmoc solid phase peptide synthesis. As a result, we have successfully demonstrated direct peptide coupling reactions as well as the synthesis of a small cyclic peptide. The Dmaoc/Dbz strategy would expand the chemical toolbox for the synthesis of functionalized peptides and contribute to the development of new peptide drugs.